Is the National Institute of Health Stroke Scale a valid prognosticator of the aftermath in patients with ischemic stroke? - Kavitha Ramachandran; Devarajan Radha; Archana Gaur; Ariyanachi Kaliappan; Varatharajan Sakthivadivel (Journal of Family Medicine and Primary Care, 2022)
Background: Cerebrovascular disease is the second most common cause of death in people more than 60 years of age. Predicting the outcome of the stroke is a great challenge for physicians. Various risk factors such as age, sex, co-morbidities, smoking and alcohol habits, type of stroke, National Institute of Health Stroke Scale (NIHSS) score, modified Rankin Scale (mRS), and others play the role in the outcome of stoke. Aim: To assess the degree of impact of NIHSS score in comparison to the other traditional risk factors on the functional outcome and 30-day mortality by mRS in the patients with acute ischemic stroke. Materials and Methods: Patients with acute ischemic stroke and age more than 18 years were included. Their admission NIHSS score and the 30-day mRS were analyzed. Patients were divided into two groups as survivors and non-survivors. Results: The mean age of survivors and non-survivors was 59.77 ± 10.99 and 65.58 ± 6.67 years, respectively. The NIHSS score on day 1 for non-survivors was 21.21 ± 8.21, and almost half of this score was seen in survivors. The NIHSS score on day 1 had a significant association with mortality with a relative risk of 0.79 (95% CI = 0.70–0.89). The NIHSS score has 73.7% sensitivity and 74.1% specificity with cutoff value of 15.5 for discriminating the outcome of ischemic stroke. Conclusion: The NIHSS and mRS scales are simple, validated, easily applicable, and reliable tools for assessing the mortality and the functional outcome of ischemic stroke patients.